Revisiting Brenda Almond’s view of Human Bonds (Philosophy and Progress, 2019)
In the prehistoric time, there was an inclination of human beings to protect their existence by living in societies. They confine themselves in the society because of having their qualities of mutual love and amity. The general tendencies of human beings are to develop bonds. These bonds happen in various ways. Society cannot survive without bonds. Bonds have significance in philosophical discussion. In the history of contemporary philosophy, applied philosophy is one of the several other aspects. Applied philosophy deals with Human rights, Euthanasia, Feminism, Abortion, Animal rights, Bonds etc. Brenda Almond, a leading figure in applied philosophy, has offered arguments in favor of her viewpoint regarding the importance of human bonds. In this paper, Almond‟s view on the nature and significance of bond has been analyzed. However, bond has also been studied from ethical perspective in this paper. And finally, it is claimed that marriage and cosmopolitanism make bonds stronger.Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 147-164